Observation of new magnetic ground state in frustrated quantum antiferromagnet spin-liquid system Cs2CuCl4 - Kim, Hyeong-Jin; Haines, C.R.S.; Liu, C.; Chun, Sae Hwan; Kim, Kee Hoon; Yi, H.T.; Cheong, Sang-Wook; Saxena, Siddharth S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Cs2CuCl4 is known to possess a quantum spin-liquid phase with antiferromagnetic interaction below 2.8 K. We report the observation of a new metastable magnetic phase of the triangular frustrated quantum spin system Cs2CuCl4 induced by the application of hydrostatic pressure. We measured the magnetic properties of Cs2CuCl4 following the application and release of pressure after 3 days. We observed a previously unknown ordered magnetic phase with a transition temperature of 9 K. Furthermore, the recovered sample with new magnetic ground state possesses an equivalent crystal structure to the uncompressed one with antiferromagnetic quantum spin-liquid phase.